2014
DOI: 10.1002/2013ja019513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of magnetospheric ELF/VLF wave amplification from the Siple Transmitter experiment

Abstract: Controlled experiments with dedicated ground-based ELF/VLF (0.3-30 kHz) transmitters are invaluable in investigating nonlinear whistler mode wave-particle interactions in the Earth's magnetosphere.The most productive such experiment operated between 1973 and 1988 near L = 4 at Siple Station, Antarctica. A major effort has been undertaken to digitize and preserve a significant portion of the historical data set from the original magnetic tapes, and we describe here the data set and the processing techniques use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
(77 reference statements)
5
21
0
Order By: Relevance
“…The use of these larger number of MDIAG transmissions provides an improved statistical understanding of wave amplification behavior of injected whistler mode waves, as presented in Figures c–e. This improves on the results presented in Li et al [] and even more so on statistics from earlier work such as Helliwell and Katsufrakis [] and Helliwell et al []. Figure c shows a histogram of the nonlinear growth rates, which ranges from 3 dB/s to 270 dB/s with a median growth rate of 68 dB/s.…”
Section: Updated Siple Statisticssupporting
confidence: 86%
See 2 more Smart Citations
“…The use of these larger number of MDIAG transmissions provides an improved statistical understanding of wave amplification behavior of injected whistler mode waves, as presented in Figures c–e. This improves on the results presented in Li et al [] and even more so on statistics from earlier work such as Helliwell and Katsufrakis [] and Helliwell et al []. Figure c shows a histogram of the nonlinear growth rates, which ranges from 3 dB/s to 270 dB/s with a median growth rate of 68 dB/s.…”
Section: Updated Siple Statisticssupporting
confidence: 86%
“…In order for Siple signals to be observed in the conjugate hemisphere, they must propagate in the magnetosphere within field‐aligned density irregularities known as ducts [ Angerami , ]. The reception of signals transmitted from Siple is more likely when geomagnetic conditions are less disturbed [ Carpenter and Bao , ; Li et al , ]. This requirement for quieting in Kp was also observed in wave injection experiments using the HAARP ionospheric heater [ Golkowski et al , ] and was attributed to the formation of stable ducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation coefficient between noise power and amplification ratio in that range of r is −0.46( p < 0.01). Li et al [] reported that the primary contribution to the increase in noise power for Siple receptions is the occurrence of natural emissions such as hiss, as seen in Figure c, and as such, intervals of higher noise power likely indicate when the conditions for linear growth are enhanced. As applied to Figure c, lower noise power suggests lower linear growth rates which are then associated with higher amplification ratios.…”
Section: Statistical Observations From 1986mentioning
confidence: 99%
“…The experiment yielded a vast amount of data, most of which continue to lack satisfactory theoretical explanation. Fortunately, the data from the experiment have been diligently digitized and are available for further study (Li et al, ).…”
Section: Observationsmentioning
confidence: 99%